Elucidating the role of SNARE syntaxin 1A in regulating lysosome and melanosome function - Bhatt, Anshul Milap; Setty, Subba Rao G advised (Bangalore : IISc, 2023)
NAREs are transmembrane proteins that localize to specific membranes and facilitate the process of membrane/vesicle fusion. SNAREs mediate the fusion by binding with their respective cognate SNAREs. SNAREs mediate the fusion by binding with their respective cognate SNAREs. The typical structure of a SNARE contains a SNARE motif which consists of typically 60-70 amino acids and interacts with other cognate SNAREs; the N-terminal regulatory; and the transmembrane domain (TM) at the C-terminus. Exceptionally, only some SNAREs may have a TM domain or an unstructured N-terminal region (Fasshauer, 2003). Further, SNAREs are classified into Q- and R- SNAREs. The Q-SNARE family comprises several members of syntaxins (STX), including STX1A and STX1B, which were extensively described in the literature. STX1A or 1B SNAREs are believed to function only in neuronal cells. However, further studies have shown that they are present in other cells as well (Bennett, Calakos, & Scheller, 1992) (Bennett et al., 1993). Studies have also shown that STX1A localizes to endosomes (Brandhorst et al., 2006).
include bibliographic reference and index
PhD; 2023; Microbiology and cell biology
Keywords: SNAREs; Vesicular trafficking; Lysosomes; Melanosomes